The clinical relevance of formal thought disorder in the early stages of psychosis: results from the PRONIA study - Oeztuerk Oemer Faruk; Pigoni Alessandro; Wenzel Julian; Haas Shalaila S.; Popovic David; Ruef Anne; Dwyer Dominic B.; Kambeitz-Ilankovic Lana; Ruhrmann Stephan; Chisholm Katharine; Lalousis Paris; Griffiths Sian Lowri; et al. (SPRINGER HEIDELBERG, 2022)
Background Formal thought disorder (FTD) has been associated with more severe illness courses and functional deficits in patients with psychotic disorders. However, it remains unclear whether the presence of FTD characterises a specific subgroup of patients showing more prominent illness severity, neurocognitive and functional impairments. This study aimed to identify stable and generalizable FTD-subgroups of patients with recent-onset psychosis (ROP) by applying a comprehensive data-driven clustering approach and to test the validity of these subgroups by assessing associations between this FTD-related stratification, social and occupational functioning, and neurocognition.
Methods 279 patients with ROP were recruited as part of the multi-site European PRONIA study (Personalised Prognostic Tools for Early Psychosis Management; www.pronia.eu). Five FTD-related symptoms (conceptual disorganization, poverty of content of speech, difficulty in abstract thinking, increased latency of response and poverty of speech) were assessed with Positive and Negative Symptom Scale (PANSS) and the Scale for the Assessment of Negative Symptoms (SANS).
Results The results with two patient subgroups showing different levels of FTD were the most stable and generalizable clustering solution (predicted clustering strength value = 0.86). FTD-High subgroup had lower scores in social (p(fdr) < 0.001) and role (p(fdr) < 0.001) functioning, as well as worse neurocognitive performance in semantic (p(fdr) < 0.001) and phonological verbal fluency (p(fdr) < 0.001), short-term verbal memory (p(fdr) = 0.002) and abstract thinking (p(fdr) = 0.010), in comparison to FTD-Low group.
Conclusions Clustering techniques allowed us to identify patients with more pronounced FTD showing more severe deficits in functioning and neurocognition, thus suggesting that FTD may be a relevant marker of illness severity in the early psychosis pathway.